CONTEXT OF LEGAL REGULATION AS BASIS FOR INTERPRETING LEGAL NORMS (ON THE EXAMPLE OF THE INTERPRETATION OF CRIMINAL-LEGAL NORMS) - Markosyan, Misak (State and Law, 2022)
Normative legal acts contain special terminology, which is often not understood univocally, evaluative concepts that require clarification in relation to a specific case, ambiguous or polysemous words and expressions that are the result of incorrect implementation of the rules of legislative technics. In addition, legal norms are interconnected, applied systematically, which require the need to identify content-logical connections between applicable norms. All these factors determine the necessity to interpret the Law. The article is devoted to the study of one of the bases of interpretation of legal norm-the context of legal regulation. The author reveals the content of general concepts of hermeneutics, such as text, context, hermeneutic circle. The article reveals the peculiarities of the interpretation of legal texts, studies the influence of the context on understanding text of a legal norm. Theoretical analyses are combined with specific examples of the interpretation of criminal-legal norms.
Keywords: interpretation of law; text; context; legal hermeneutics; hermeneutic circle; normative legal act; criminal legal norm